2011
DOI: 10.1673/031.011.8601
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of the Scorpion,Microtityus jaumeiin Sierra de Canasta, Cuba

Abstract: An assessment of the population dynamics of Microtityus jaumei Armas (Scorpiones: Buthidae) on the slopes south of Sierra de Canasta, Guantánamo Province, Cuba show an increase in activity over the year (≤ 0.05). The activity peak is related to the reproductive period from June to November. The abundance of scorpions was significantly related to density of the canopy and thickness of the substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…2) It is assumed that the warmer seasons are the time of reproduction for scorpions [35][36]. The important point is that the scorpions stings happen entire a year.…”
Section: Discussionmentioning
confidence: 99%
“…2) It is assumed that the warmer seasons are the time of reproduction for scorpions [35][36]. The important point is that the scorpions stings happen entire a year.…”
Section: Discussionmentioning
confidence: 99%
“…There are two reasons behind this fact: 1) scorpions are ectothermal animals; therefore, their activities increase with the increase of the environmental temperature. It is assumed that the warmer seasons are the time of reproduction for scorpions ( Cala-Riquelme and Colombo 2010 ). However, in the tropics, scorpions are active all year long, although they are more active during the hotter months ( Spirandeli-Cruz 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that surface activity of total scorpions was higher in mature forest than in secondary forest with the UV light method for most of the months. Some species of scorpions reach their highest densities only in areas with extensive ground cover from rocks, logs, other vegetation litter, canopy density and the thickness of the substrate (Cala-Riquelme and Colombo 2011;Koch 1978;Prendini 2001;Smith 1966;Stahnke 1966;Warburg and Ben-Horin 1978). This higher abundance could be due to characteristics of the habitat in mature forest that favour a high density.…”
Section: Discussionmentioning
confidence: 99%
“…The number and percentages of species caught were different in both methods. Pitfall traps do not show the actual surface activity, but depend more on the behaviour of each species: wanderer species are more easily caught by the trap than sit-and-wait ones (Acosta 1995b;Cala-Riquelme and Colombo 2011). Pitfall traps show both fewer specimens and fewer species than UV light.…”
Section: Discussionmentioning
confidence: 99%